Variation in nestling body condition and wing development predict cause‐specific mortality in fledgling dickcissels. (21st October 2016) - Jones, Todd M.; Ward, Michael P.; Benson, Thomas J.; Brawn, Jeffrey D.
Abstract : Phenotypic traits developed in one life‐history stage can carryover and affect survival in subsequent stages. For songbirds, carryover effects from the pre‐ to post‐fledging period may be crucial for survival but are poorly understood. We assessed whether juvenile body condition and wing development at fledging influenced survival during the post‐fledging period in the dickcissel Spiza americana . We found pre‐ to post‐fledging carryover effects on fledgling survival for both traits during the 'early part' – first four days – of the post‐fledging period. Survival benefits of each trait depended on cause‐specific sources of mortality; individuals in better body condition were less likely to die from exposure to adverse environmental conditions, whereas those with more advanced wing development were less likely to be preyed upon. Fledglings with more advanced wing development were comparatively more active and mobile earlier in the post‐fledging period, suggesting they were better able to avoid predators. Our results provide some of the first evidence linking development of juvenile phenotypic traits to survival against specific sources of post‐fledging mortality in songbirds. Further investigation into pre‐ to post‐fledging carryover effects may yield important insights into avian life‐history evolution.